Motivação para coprodução do bem público: construção de uma escala - Bezerra, Joacil Carlos Viana (2020)
This research had as main objective the construction of a scale to measure the aspects that motivate the citizen to participate in the co-production of the public good, through civil society organizations. The method followed for the construction and validation of the scale on motivation for the co-production of the public good, is related to the 10 steps proposed by Costa (2011). The research started with an integrative literature review, aiming to identify studies with an approach on motivation for co-production and to identify aspects that favor citizen engagement in the provision of public services through civil society organizations. From the review, items were generated to be used in two sampling activities, with the application of questionnaires prepared with the Google Forms tool. The study is quantitative in nature and went through exploratory and descriptive steps with the data analyzed using the SPSS and R software through preliminary exploratory analysis, correlation analysis, exploratory and confirmatory factor analysis, reliability and construct validity. After performing the steps and the methodological procedures, the scale for motivating the coproduction of the public good was presented, composed of four dimensions (self-efficacy, nature of the service, sociability and perceived relevance) and twelve items. In addition to seeking to fill a gap in the literature, the scale can be useful to public managers and civil society organizations, especially with regard to people management. The main contribution of this work is its originality in building a scale of motivation for the co-production of the public good in the Brazilian context. Another contribution of the research is to be able to inform managers about the incentive strategies to be used in order to increase the participation of citizens in the provision of public services. As a suggestion for new studies, it is possible to point out a research to identify the effects of individual and group coproduction and the realization of a research to test the validity of the scale on motivation for coproduction of the public good in other contexts.